A study of the Gospels in Codex Alexandrinus : codicology, palaeography, and scribal hands - Smith, W. Andrew. (New Testament Tools, Studies and Documents, 2014)
Codex Alexandrinus is one of the three earliest surviving entire Greek Bibles and is an important fifth-century witness to the Christian Scriptures, yet no major analysis of the codex has been performed in over a century. In A Study of the Gospels in Codex Alexandrinus W. Andrew Smith delivers a fresh and highly-detailed examination of the codex and its rich variety of features using codicology, palaeography, and statistical analysis. Among the highlights of this study, W. Andrew Smith's work overturns the view that a single scribe was responsible for copying the canonical books of the New Testament and demonstrates that the orthographic patterns in the Gospels can no longer be used to argue for Egyptian provenance of the codex.